Edification through the memory of sins - Chrissidis, Nikolaos A. (Canadian-american Slavic Studies, 2018)
The article explores the practical uses of Eastern Orthodox indulgences as certificates of absolution with a dual function (as mnemonic tools and as public certificates of good standing with the church) in the early modern period. © KONINKLIJKE BRILL NV, LEIDEN, 2018
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00325 tex.type: [object Object]
Keywords: Eastern Orthodox indulgences; Eastern Orthodox penitential practices; Mese katastasis ton psychon; Patriarch Dositheos of Jerusalem; Purgatory; Synchorochartia; dept.his; peer-reviewed